INDONESIA’S NATURAL GAS: PRODUCTION, RESERVES, AND CHALLENGES - Bambang Widarsono (Scientific Contributions Oil and Gas, 2007)
Recent years has witnessed decline in national oil production at an alarming rates of  higher than 10% annually. On the other hand, national gas reserves and production situation  is much better even though problems such as unanticipated production shortfall of  existing fields and commerciality of new reserves have still to be faced. Analysis on history  of production and reserves and comparison between oil and gas discoveries in recent years  may lead into a conclusion natural gas may serve as an alternative source for energy and  national income in years ahead. However, challenges such as technology, infra-structures,  law enforcement, social unrests, tight regulations, and incentives are still day-to-day  reality. These challenges need to be addressed appropriately if sustainable gas, and also  oil, productions are to be achieved.